The Influence of Entrepreneurs’ Psychological Capital on Their Deviant Innovation Behavior - Xu, Wenhai; Zhao, Shouzheng (Frontiers in Psychology, 2020)
The study aims to change the innovation consciousness and creative thinking of enterprises, improve the innovation and creative ability of enterprises, and explore the influence of psychological capital on the deviant innovation behavior, thereby realizing the application and development of positive psychology in the field of innovation and creation. The influence of entrepreneurial psychological capital on deviant innovation behavior was discussed. First, the data were obtained based on the questionnaire, and the Likert scale was selected to measure the variables effectively. Second, SPSS 21.0 software combined with statistical analysis method, a statistical analysis was made on the correlation among deviant innovation, psychological capital, work values, and work remodeling. Third, using the analytic hierarchy process (AHP), the relationship between psychological capital and deviant innovation behavior was explored. The results showed that the reliability of each scale was good, Cronbach's  coefficients were all higher than 0.8, and the fitting effect of the four-factor model was the best, showing the highest differentiation validity. There were significant correlations among entrepreneur's psychological capital, entrepreneur's work values, and enterprise employees' work remodeling and deviant innovation behavior, among which the psychological capital and work values was the most correlated with deviant innovation. With the psychological capital of entrepreneurs as the adjustment variable and the interaction added, the explanation rate of the level equation was increased from the initial 17% to 24.2%. To sum up, the psychological capital of entrepreneurs plays a very good role in regulating work values and deviant innovation behavior. In the current environment of innovation and entrepreneurship development, entrepreneurs should give full play to the regulatory role of their own psychological capital, enhance their own deviant innovation and development, and encourage their employees to actively deviant innovation behavior.